Effect of Feed with Different Energy-protein Ratios on Parameters of Sheep Ruminal Fermentation - Mawati, Sri; Adi, Agung Purnomo; Soedarsono; Sunarso (Pakistan Journal of Nutrition, 2016)
Background: The development of sheep farming has a strategic role in efforts to fulfill protein requirements from animal-originated food. However, the farming of ruminants has environmental impacts on water, soil and air. The pollution from these impacts can be controlled externally and internally. Internal control is achieved through improvement in livestock production efficiency, which is possible with the provision of rations that supply protein of the quality and in the amounts appropriate to meet animal requirements and farming objectives. Objective: This study was conducted to increase productivity of sheep and control pollution impact by manipulating the energy-protein ratio of feed. Methodology: In an experiment, the six complete feed formula were fed to sheep with the following protein-energy ratios: 0.158, 0.166, 0.195, 0.198, 0.230 and 0.272. Feed was provided at 4% b.wt., twice a day, i.e., morning and afternoon. In rumen fluid, the following parameters of rumen fermentation were examined: pH, volatile fatty acids and NH3. Results: In all treatments, the pH of rumen fluid was higher before eating (0 h) than at 3 and 6 h post-feeding. Treatment with different protein-energy ratios of feed significantly affected the pH and VFA and NH3 content of the rumen fluid. Conclusion: The adjustment of the protein-energy ratio of feed can be used as a strategy to control pollution as the production of farming sheep increases. The decline in nitrogen pollution to the environment will reduce negative impacts on the environment damage, thereby improving the health of livestock farmers.